Politik Hukum Islam di Indonesia: Studi Terhadap Legislasi Kompilasi Hukum Islam (KHI) - Sirojudin Ahmad (Justicia Islamica, 2004)
This study aims to analyze the politics of Islamic law in Indonesia through a study of the process of legislating the Compilation of Islamic Law (KHI). The method used is normative juridical research with a historical and legal policy approach, through the analysis of legislation documents, government policies, and the social dynamics behind the drafting of the KHI. The results show that the KHI legislation is a compromise between Islamic norms and state policy in building a harmonious legal system. The KHI plays an important role in the unification of Islamic law in Indonesia, although it still faces challenges in its implementation, especially related to the diversity of schools of thought and social change. This study emphasizes that the politics of Islamic law in Indonesia is dynamic and influenced by the interests of the state and the aspirations of Muslims in the formation of regulations that are more responsive to the needs of society.